The Rights of the Child and a Problem of Immigration Detention - Markiewicz-Stanny, Joanna (Polish Review of International and European Law, 2020)
The problem of children immigration detention will be explored based on the analysis of international human rights law and international refugee law. Preliminary remarks will elaborate on how migration detention impacts on the exercise of the rights of the child, focusing, in particular, on the deleterious influence this measure exerts on the child’s mental well-being. Next, the principle of using child migration detention as a measure of last resort will be analysed in light of international standards. The practical implementation of this principle calls for observing the standards for individual assessment of the particular situation of each immigrant child. This includes treating the minors first and foremost as children, and only then as immigrants. Another key element is the area of the state’s positive obligations. International case law has increasingly called for an absolute obligation to first provide the child or the family with a child with an alternative to the detention measure. This involves the need to establish the necessary infrastructure that would allow for such an alternative solution. Furthermore, in a situation where detention is necessary, it should be exercised while accommodating the needs of families with children. As will be demonstrated, nonfeasance and negligence lead, in the most extreme cases, to their being recognised as violation of the prohibition of inhuman or degrading treatment or punishment.